Libyan religious beliefs and their relationship to the ancient Near East beliefs - sahnine, nadjia (Journal of Social Sciences and Humanities, 2023)
Libya the ancient name of the ancient Maghreb, a civilized geographic framework that extends from the west of the Nile in the east to the Atlantic in the west, its historical roots goes back to prehistoric, The Libyan civilization arose with the dawn of history on 3200 BC and extended until the establishment of Carthage on its territory 814 BC by the Phoenicians, transfer of material and written resources in the study of aspects especially the religious ideological aspect, the reason that stood in the way of scholars and researchers to gain access to the reality of the old Libyan religious belief and its peculiarities, The researchers' studies were based on the interpretation of rock painting and Petroglyphs that were often found in the Sahara Desert, and relying on the inscriptions of the Egyptian pyramids and graves, as well as the Phoenician monuments and legends, and the writings of Greek historians, especially the historian Herodotus, to know the nature and steps of the Libyan belief, And its idol and rituals and the relationship of impact and influence of eastern beliefs especially the Egyptian and the Phoenician, By virtue of the conflict and coexistence relationships I have gathered , and the conclusion of the extent of mutual religious quotation and religious coexistence between the Maghreb and the Eastern civilization, and the knowledge of the local deities from the foreign arrivals in the old Libyan religious belief